Study of the Influence of Price, Service Quality, Satisfaction, and Repurchase Intentions at Citramulia Travel and Tour Lombok: Kajian Pengaruh Price, Service Quality, Satisfaction, dan Repurchase Intentions di Citramulia Travel and Tour Lombok - Rita Alfin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2024)
This study investigates the impact of price and service quality variables on repurchase intentions in the context of travel services and tour operator activities post the Covid-19 pandemic. It explores whether consumer satisfaction mediates the relationship between price, service quality, and repurchase intentions. Using a quantitative explanatory research design, the study involves a sample of 110 individuals intending to purchase Travel services and tour operator activities from Citramulia Travel and Tour Lombok between the post-Covid-19 period and December 2022. Data collection entails distributing questionnaires after instrument validation and reliability checks. Analysis shows that prices have a non-significant, negative effect on repurchase intentions, while service quality significantly and positively influences repurchase intention. Consumer satisfaction plays a significant role in enhancing repurchase intentions. Affordable pricing positively affects consumer satisfaction, leading to increased repurchase intentions. However, certain aspects of service quality, like reliability, responsiveness, and tangibles, negatively impact overall satisfaction. Consumer satisfaction partially mediates the relationship between price and repurchase intention. In contrast, it does not mediate the association between service quality and repurchase intention, as the direct positive effect of service quality on repurchase intention remains. This study offers insights into the interplay among price, service quality, consumer satisfaction, and repurchase intentions in the post-Covid-19 travel services and tour operator activities landscape.